Leptospirosis Presenting with Features of Thrombotic Microangiopathy - Chaudhry Adeel Ebad; Nabeehah Moollan; Adeel Rafi Ahmed; Anthony Dorman; Colm Magee (Case Reports in Nephrology)
Leptospirosis is an exceptionally rare infectious disease in the Republic of Ireland. Leptospirosis can present with or mimic thrombotic microangiopathies (TTP/HUS). A 48-year-old male presented to a peripheral hospital with a short history of diarrhoea, anaemia, hyperbilirubinemia, raised lactate dehydrogenase, thrombocytopenia, and severe acute kidney injury and was transferred to our tertiary care kidney centre. A form of acute thrombotic microangiopathy (TMA) was suspected. However, no schistocytes were seen on the blood film, and the reticulocyte count was depressed. A kidney biopsy was performed before initiating any potential treatment which revealed acute interstitial nephritis (AIN). Leptospirosis was considered and subsequently serologically confirmed. The patient was managed with antimicrobials and supportive therapy. Acute kidney injury is common in leptospirosis and is often due to AIN. Initial presentation can mimic TMA; however, a differential diagnosis of leptospirosis should be considered even in nonendemic areas due to re-emergence of the disease.